Identification of sperm motility subpopulations in Gyr falcon (Falco rusticolus) ejaculate: a tool for investigating between subject variation - Fahimeh Seyedasgari; Behnam Asadi; Sandor Sebastyen; Roberto Guillen (The Korean Society of Animal Reproduction and Biotechnology, 2022)
Subgroups of sperm which share similar motility features documented in mammals indicate between-subject variations that might be related to fertilizing potential of the respective ejaculates. The objectives of this study were to define subpopulations of motile sperm in Gyr falcon semen using kinematic parameters driven by Computer Assisted Semen Analysis (CASA) and to investigate the subjectrelated variations in these subpopulations. A total of 24 fresh ejaculates from 6 falcons were used to assign each of the 20473 sperms into 3 subpopulations by a multivariate cluster analysis. The proportion of sperms in different sub-populations were compared among subjects by a generalized linear model and repeatability of sperm frequency in different subpopulations was investigated by corelation analysis. The resulting 3 categories of sperm indicated significant differences in all kinematic parameters (p < 0.05). Subpopulation 1 (15.91%) contained sperms with the highest velocity and progressiveness of movement trajectory while subpopulation 3 (6.4%) included the least progressively motile sperms. Proportion of rapid and medium progressive sperm were consistently higher in the ejaculate of three falcons compared to the two other birds which also had the highest proportion of slow non-progressive sperms (p < 0.05). Respective proportion of sperms in each subpopulations indicated significant repeatability over multiple measurements (p < 0.05). In conclusion, subpopulations of motile sperm in Gyr falcon can be identified using kinematic parameters generated by CASA. Individual differences in the proportion of these subpopulations might have potential application for identifying the males with higher fertilizing capacity.